The growing demand for expert certification in electric vehicle technology in Israel - Avital, Kobi [Verfasser] (My University, 2026)
"This paper examines Israel’s shift to electric mobility and highlights the growing shortage of skilled professionals and the rising demand fo certified trainings." (authors' abstract; BIBB-Doku)
Keywords: S 6.3.2 Techniker, Technische Sonderkräfte, Zeichner, Industriemeister (ausgenommen IT-Berufe); I 2.3.4 Asien; 370; Elektromobilität; Kraftfahrzeugtechniker; Kraftfahrzeugtechniker; Fachkräftemangel; Israel